Optimasi Slice Thickness dengan Nilai Signal to Noise Ratio dan Contrast to Noise Ratio untuk Meningkatkan Kualitas Citra MRI Genu - Agnes Maria Salvi Anastasia Victor; Gusti Ngurah Sutapa; A. A. Ngurah Gunawan; I Nengah Sandi; Ni Nyoman Rupiasih; I Nengah Simpen (Universitas Hamzanwadi, 2025)
Research has been conducted on the effect of slice thickness variation on the quality of Genu MRI images. This study was conducted at the Radiology Installation of Bali Mandara Hospital using primary data from Genu MRI examination results.The independent variable in this study is the variation of slice thickness values of 3, 5, and 7 mm. There were 30 patientsmeasured and the tissues analyzed were ligament, bone, fat, and noise as background using the ROI method and the segmentation results wereresults were taken at the mean value and standard deviation in the background. The difference in SNR and CNR values due to variations in slice thickness values can be tested using the Factorial Anova test. The results of this study obtained that there is an effect of slice thickness variation on SNR and CNR values that will have an impact on the quality of MRI Genu images. The greater the slice thickness value analyzed, the greater the SNR and CNR values produced and the better the image quality. In ligament tissue, the average SNR values of 3, 5 and 7 mm are 23.830; 36.594; and 50.524, respectively. In bone tissue, 191.352; 277.399, and 344.170 were obtained. In fat tissue, SNRs of 9,460, 292,022, and 367,463 were obtained. Changing the slice thickness will directly affect the SNR. It can be seen that the higher the slice thickness value given, the higher the SNR and CNR values for each tissue evaluated and the longer the scanning time required. In the slice thickness variation.